Combination Therapy for the Treatment of Pancreatic Cancer - Greenhalf, William; Thomas, Amy (Anti-Cancer Agents in Medicinal Chemistry, 2011)
Treatment of pancreatic cancer should be a relatively simple clinical problem, all that is needed is to find the features of pancreatic cancer cells that distinguish them from normal cells and target these differences. This is the basis of current therapies including gemcitabine and 5-FU which target DNA synthesis. Unfortunately, cancer cells become resistant to these therapies: By exclusion of drugs from cancer cells; by changes in enzymes metabolising the drugs; or by becoming more resistant to stress and apoptosis. Increasing levels of the drugs is limited by their somatic toxicity so numerous alternative therapies have been proposed. Testing these alternatives in clinical trials will be difficult unless they work with the standard treatments (e.g. gemcitabine). To date most work has concentrated on combining different S-phase targeting agents. Further incremental increase in survival benefit should be possible by targeting resistance to apoptosis, targeting stroma or even targeting multiple pathways in combination with gemcitabine.
Keywords: targets